Several Theoretical Aspects of Constitutional Dynamics- Adoption and Amendment of the Constitution - Jelena Trajkovska Hristovska (My University, 2021)
The paper "Several Theoretical Aspects on Constitutional Dynamics - adoption and amendment of a constitution" analyzes one very important issue of constitutional law- constitutional dynamics. The paper analyzes several theoretical aspects of two significant phenomena that represent materia constitutionis. These two phenomena, reveal many dilemmas and issues to which constitutional law pays due attention, especially the latter one, because the stability of the constitution as a construction depends on the constitutional dynamics, and therefore the stability of the established system as a whole. The paper analyzes the issues related to the procedure for adopting the constitution - the first constitution in a country and a new constitution in an existing state. The paper provides an overview of the basic ways of adopting the constitution supported by examples from the constitutional history. The paper also elaborates on the issue of constitutional revision. Special attention is given to the matter of meaning and conditionality of constitutional revision, the factual and formal change of the constitution. Finally, the paper provides a comparative overview of constitutional solutions about the prohibitions against constitutional revision, their meaning and significance
Keywords: constitution, adoption of the constitution, revision of the constitution, amendments, prohibitions against the revision of the constitution, revision models